Mitophagy Protects the Retina Against Anti-Vascular Endothelial Growth Factor Therapy-Driven Hypoxia via Hypoxia-Inducible Factor-1α Signaling - Sun, Yimeng; Wen, Feng; Yan, Chun; Su, Lishi; Luo, Jiawen; Chi, Wei; Zhang, Shaochong (Frontiers in Cell and Developmental Biology, 2021)
Anti-VEGF drugs are first-line treatments for retinal neovascular diseases, but these anti-angiogenic agents may also aggravate retinal damage by inducing hypoxia. Mitophagy can protect against hypoxia by maintaining mitochondrial quality, thereby sustaining metabolic homeostasis and reducing reactive oxygen species (ROS) generation. Here we report that the anti-VEGF agent bevacizumab upregulated the hypoxic cell marker HIF-1α in photoreceptors, Müller cells, and vascular endothelial cells of oxygen-induced retinopathy (OIR) model mice, as well as in hypoxic cultured 661W photoreceptors, MIO-MI Müller cells, and human vascular endothelial cells. Bevacizumab also increased expression of mitophagy-related proteins, and mitophagosome formation both in vivo and in vitro, but did not influence cellular ROS production or apoptosis rate. The HIF-1α inhibitor LW6 blocked mitophagy, augmented ROS production, and triggered apoptosis. Induction of HIF-1α and mitophagy were associated with upregulation of BCL2/adenovirus E1B 19-kDa protein-interacting protein 3 (BNIP3) and FUN14 domain containing 1 (FUNDC1), and overexpression of these proteins in culture reversed the effects of HIF-1α inhibition. These findings suggest that bevacizumab does induce retinal hypoxia, but that concomitant activation of the HIF-1α-BNIP3/FUNDC1 signaling pathway also induces mitophagy, which can mitigate the deleterious effects by reducing oxidative stress secondary. Promoting HIF-1α-BNIP3/FUNDC1-mediated mitophagy may enhance the safety of anti-VEGF therapy for retinal neovascular diseases and indicate new explanation and possible new target of the anti-VEGF therapy with suboptimal effect.